The Status of Customary Tenants in Relation to Land Held by Him: An Overview of Customary Law - Otu, Michael Takim; Edet, Joseph (NAJAHA, 2023)
The article seeks to examine the effects of the Land Use Act of 1978 on the customary system of land holding in Nigeria. Since the birth of the Act, the problem facing our courts, ordinary people and lawyers is determining the actual position of customary tenants under the system of property rights introduced by the Law. The empirical legal research method used in this study is a type of qualitative research. This method focuses on cases in the community using legal studies, while the scope of this research is the Land Use Act 1978 against the customary land tenure system in Nigeria. The results of the discussion made it clear that the Laws on Land Use and Customary Land Owners have much in common. As such, the controversies generated by these issues continue to defy consensus among our academic